2011
DOI: 10.1002/lsm.21136
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial electrical conduction block induced by photosensitization reaction in exposed porcine hearts in vivo

Abstract: The results suggest that the photosensitization reaction might induce acute and chronic myocardial electrical conduction block. Cardiac ablation with the photosensitization reaction might be a non-temperature-mediated methodology for arrhythmia therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…In our previous report, a successful PDTmediated conduction block using a simple silica optical fiber with 208 J/cm 2 of irradiation induced a maximum temperature increase of 12.8°C measured by an infrared thermal camera. 12 Because infrared thermal cameras are subject to errors attributable to the use of red laser light, we used various temperature monitors in this study and developed a new PDT laser catheter, which also enabled us to monitor backscattering of the laser and avoid blood charring attributable to any sudden temperature increase. 16,17 The present study clearly demonstrated that lesion induction by PDT was not mediated by heat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous report, a successful PDTmediated conduction block using a simple silica optical fiber with 208 J/cm 2 of irradiation induced a maximum temperature increase of 12.8°C measured by an infrared thermal camera. 12 Because infrared thermal cameras are subject to errors attributable to the use of red laser light, we used various temperature monitors in this study and developed a new PDT laser catheter, which also enabled us to monitor backscattering of the laser and avoid blood charring attributable to any sudden temperature increase. 16,17 The present study clearly demonstrated that lesion induction by PDT was not mediated by heat.…”
Section: Discussionmentioning
confidence: 99%
“…A custom-made 4-polar 7-French deflectable laser catheter was placed at the isthmus and manipulated as for the radiofrequency ablation procedure and reported in previous studies. 6 Because our previous study showed that a total of 300 J/cm 2 was required to obtain the acute conduction block in a porcine model, 12 we set the irradiance to 10 W/cm 2 and the duration of each irradiation to 30 seconds by a point-by-point fashion to prove the nature of nonthermal ablation. According to previous reports, intercaval and connected transverse lesions were required to ensure the establishment of a CTI conduction block in the canine atrial flutter ablation model.…”
Section: Ablation Proceduresmentioning
confidence: 99%
“…In radio- frequency ablation therapy for tachyarrhythmia, severe thermal changes cause complications to arise [9,10]; therefore, ablation methods that minimize thermal damage to the myocardium should be developed. A new application of the photosensitization reaction for myocardium electrical conduction block to tachyarrhythmia has been proposed [11][12][13]. Ito et al used Talaporfin sodium and rat myocardial cells to investigate in vitro photosensitization reactions with short drug-light intervals.…”
Section: Introductionmentioning
confidence: 99%
“…Severe thermal complications such as cardiac tamponade, pulmonary vein stenosis, cerebral infraction, phrenic nerve injury, and esophageal fistula are the problem [2]. We have proposed to apply the extracellular photosensitization reaction as a new non-thermal treatment methodology for tachyarrhythmia [3][4][5][6]. We intended to obtain the electrophysiological conduction block performance by oxidation of singlet oxygen produced by the extracellular photosensitization reaction with short drug-light interval.…”
Section: Introductionmentioning
confidence: 99%